Neuroglial Differentiation and Neoplasms in Testicular Germ Cell Tumors Lack Immunohistochemical Evidence of Alterations Characteristic of Their CNS Counterparts: A Study of 13 Cases. (March 2019) - Matoso, Andres; Idrees, Muhammad T.; Rodriguez, Fausto J.; Ibrahim, Junaid; Perrino, Carmen M.; Ulbright, Thomas M.; Epstein, Jonathan I.
Abstract : Overgrowth of neuroglial tissue is rare in testicular germ cell tumors and mostly reported as isolated cases. We retrospectively reviewed 13 cases of testicular germ cell tumors from 2 institutions from 1995 to 2018. Hematoxylin and eosin slides were collected and reviewed. Immunohistochemistry was performed in all cases with available material. The series included 4 primary tumors and 9 metastases, including 8 retroperitoneal and 1 axillary lymph node (LN). The average age was 34 (range: 19 to 54). Five of the LN dissections were postchemotherapy, with one a recurrence 5 years after the initial diagnosis. The average tumor size for primary tumors was 5.15 cm (range: 1.7 to 7.3) and for metastases was 6.4 cm (range: 0.6 to 15). The largest size of the neuroglial component was 4.5 cm in the primary tumors and 7.5 cm in metastatic sites. The neuroglial component in the primary site was associated with pure teratoma (n=2) and with a mixed germ cell tumor (teratoma, seminoma, and embryonal carcinoma) (n=2). Cases involving LNs were associated with teratoma (n=4), seminoma (n=2), rhabdomyosarcoma (n=2), primitive neuroectodermal tumors (n=1), and high-grade sarcoma (n=1) (some with >1 other component). Two cases were pure glial tumor. Histologically, the neuroglial components included low-grade astrocytoma (n=3) (both with microcysts formation and pilocytic features), gemistocytic astrocytomas (n=3), anaplastic astrocytoma (n=2), ganglioglioma (n=1), glioblastoma (n=2), gliosarcoma (n=1), and developing central nervous system (CNS) (n=2). By immunohistochemistry, 13/13 (100%) cases were GFAP(+), 10/10 (100%) cases showed retained ATRX, 10/10 were IDH1 pR132H (−), 5/10 (50%) were p53 (+). A single case 1/10 (10%) was BRAF p.V600E (+), but a mutation was not identified by polymerase chain reaction. Follow-up was available in 6 patients; 4 were confirmed to have received chemotherapy with BEP; 1 had a local recurrence and the patient with gliosarcoma developed a lung metastasis morphologically similar to the gliosarcoma of the retroperitoneum. In conclusion, neuroglial differentiation and neoplasms are rare in testicular germ cell tumors and are most commonly associated with teratomas; they can be seen in primary and metastatic sites. They exhibit the full range of neuroglial differentiation including developing CNS to gliomas/glioneuronal tumors WHO grades I-IV. None of the cases showed results consistent with ATRX, IDH or BRAF alterations, suggesting they have different oncogenic mechanisms than their CNS counterparts.